2016
DOI: 10.1532/hsf.1426
|View full text |Cite
|
Sign up to set email alerts
|

Levosimendan Use Increases Cardiac Performance after Coronary Artery Bypass Grafting in End-Stage Renal Disease Patients

Abstract: No important adverse effect was detected during levosimendan infusion. Because levosimendan at a dose of 0.03-0.05 μg/kg/min increased myocardial performance significantly in the postoperative period, it can be used safely in end-stage renal disease patients undergoing isolated CABG. The requirement of vasopressors were lower in SG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A recent study using the Chang Gung Research Database from Taiwan on 52 patients with eGFR < 30 ml/min/1.73 m 2 receiving levosimendan showed similar outcomes compared to 374 patients receiving dobutamine ( 13 ). Similar results are reported from 25 patients with end-stage renal disease undergoing coronary artery bypass grafting who received levosimendan showing similar side effects compared to 33 patients on placebo ( 34 ). To the best of our knowledge no other study has shown an increase in side effects of levosimendan when used in eGFR < 30 ml/min/1.73 m 2 either.…”
Section: Discussionsupporting
confidence: 78%
“…A recent study using the Chang Gung Research Database from Taiwan on 52 patients with eGFR < 30 ml/min/1.73 m 2 receiving levosimendan showed similar outcomes compared to 374 patients receiving dobutamine ( 13 ). Similar results are reported from 25 patients with end-stage renal disease undergoing coronary artery bypass grafting who received levosimendan showing similar side effects compared to 33 patients on placebo ( 34 ). To the best of our knowledge no other study has shown an increase in side effects of levosimendan when used in eGFR < 30 ml/min/1.73 m 2 either.…”
Section: Discussionsupporting
confidence: 78%
“…The mechanism of action of levosimendan also includes the activation of adenosine triphosphate-sensitive potassium channels, which results in improved myocardial contractility, vasodilation, and cardioprotection. Results of recent clinical trials have shown that the administration of the calcium sensitizer levosimendan after cardiac surgery can improve cardiac and renal functions of patients [ 12 14 ]. However, these benefits were greatest for the cardiac surgery patients with severe valvular disease or patients with severe coronary heart disease with diminished LVEF.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IABP may have had an additional positive effect on coronary perfusion, and hence cardiac performance. Similarly, the RCTs of Anastasiadis 25 and Atalay 26 observed increases in cardiac index 24 hours and 7 days after cardiac surgery. Both studies, however, included only patients with mild or moderate left ventricular dysfunction undergoing CABG.…”
Section: Discussionmentioning
confidence: 82%